Uso de las bases nitrogenadas y su relación con la biotecnología agrícola - Moreira Ruiz, Jorge Sebastián (2025)
This research highlights the importance of using nitrogenous bases in agricultural biotechnology, which is essential to improve productivity and sustainability. In the synthesis of DNA and RNA, these molecules allow the development of biotechnological resources, considering an innovative strategy that strengthens food security and optimizes agricultural practices. The general objective of this study is to analyze the use of nitrogenous bases and their relationship with agricultural biotechnology. The methodology applied was resources from web pages, current scientific articles and books from virtual libraries, in order to collect and detail various opinions of the actors that contribute to the development of the research. The most important results indicate that the genetic manipulation of nitrogenous bases in crops such as rice, soybeans and corn has facilitated the control of environmental impact, minimizing the excessive use of fertilizers, and at the same time, optimizing nitrogen absorption. Technologies such as CRISPR.Cas9 have enabled precision gene modifications, improving desirable traits such as root nodule formation, drought, pest and disease resistance, and yield potential. In conclusion, these advances reduce the dependence on chemical fertilizers and the environmental impact, promoting more efficient agriculture by combining biotechnology with responsible agricultural practices that contribute to food security through more adaptable and nutritious crops in the long term.